Aesthetics of Negative Communication: Conflicts of Journalists and Officials - A. M. Ogorodnova (Дискурс)
Introduction. The article proposes an aesthetic aspect of describing communication between journalists and politicians. The dramaturgical, image and consumer contexts of media communication, which, in our opinion, contain an aesthetic component, are problematized. An aesthetic look at the topic traditionally attributed to political science or sociological fields of knowledge allows us to see aspects of human activity that are perhaps less noticeable, but no less influential on the reproduction of the social order.   Methodology and sources. The analysis of the situations discussed in the article is implemented in the tradition of interpretive sociology, which considers social communication as a constitutive factor in the behavior and activities of people. The principles of dramaturgical sociology of I. Hoffmann, theoretical observations of authors working in the field of symbolic politics, conceptual reasoning set out in F. Ankersmit’s essay “Political Representation” are used, in particular the term “representation” he uses in relation to the politician.   Results and discussion. Situations that can be classified as negative communication between journalists and politicians were selected for analysis. The latter is defined as an action that can provoke negative emotions and feelings of communication participants, and thus disorient them regarding the development and consequences of the communicative situation. The obtained research results confirm that the concept of “negative communication” allows us to capture not only the emotional mode of professional activity and interprofessional communication of politicians and journalists, but also to offer an aesthetic view of professional communication.   Conclusion. Situational analysis of conflicts in a professional environment, implemented in the tradition of interpretive sociology, reveals their spectacularity, predicting the forms of experience, and allows us to consider them, on the one hand, as works of art, on the other, as moral stories for social education. Aesthetic political representation is the most important need of any civil society, and its implementation is inextricably linked with political education.